Oblicz:
a) 11 + (-12) + 39 +9 – 8 =
b) -4 ½ + 1/6 + (-1/2) + 1 1/3 =
c) 45 + (-9) + (-91) + 5 =
d) 6,25 + (-1/4) + (-3/5) + 0,75 =
e) 4/7 + (-3/14) + 1/14 =
f) ½ + (-3/4) + (-5/8) =
g) 5 2/3 + (-3 4/5) + 1/3 + (-1/5) =
h) 16 4/5 + (-4.8) + 3 1/5 + (-4 1/5) =

1

Odpowiedzi

2010-01-04T19:05:45+01:00
A) 11 + (-12) + 39 +9 – 8 = 11 - 12 + 39 + 9 - 8 = 39
b) -4 ½ + 1/6 + (-1/2) + 1 1/3 = -4 1/2 + 1/6 - 1/2 + 1 1/3 = -4 + 1/6 + 4/3 = -4 + 1/6 + 8/6 = -4 + 9/6 = -4 + 3/2 = -8/2 + 3/2 = -5/2
c) 45 + (-9) + (-91) + 5 = 45 - 9 - 91 +5 = -50
d) 6,25 + (-1/4) + (-3/5) + 0,75 = 6,25 - 0,25 - 0,6 + 0,75 = 7,35
e) 4/7 + (-3/14) + 1/14 = 8/14 - 3/14 + 1/14 = 4/14 = 2/7
f) ½ + (-3/4) + (-5/8) = 4/8 - 6/8 - 5/8 = -7/8
g) 5 2/3 + (-3 4/5) + 1/3 + (-1/5) = 17/3 - 19/5 + 1/3 - 1/5 = 18/3 - 20/5 = 6 - 4 = 2
h) 16 4/5 + (-4.8) + 3 1/5 + (-4 1/5) = 16,8 - 4,8 + 3,2 - 4,2 = 11,8
29 4 29